Recovery of Bioactive Compounds from the Biomass of Aromatic Plants After Distillation Using NADES: A Sustainable Alternative Extraction Method - Eleonora Truzzi; Davide Bertelli; Benedetta Catellani; Danial Darvishi Jazi; Stefania Benvenuti (Molecules)
The extraction processes for medicinal plants, particularly the distillation of aromatic plants, generate significant quantities of by-products, consisting of fibrous biomass and hydrosols. These by-products pose challenges for disposal and recovery. Consequently, it is imperative to make the entire highly energy-intensive process more sustainable by valorizing all derivatives. This study aims to recover polyphenols from the exhausted biomasses of Artemisia dracunculus, Echinacea purpurea, Helichrysum italicum (from the Asteraceae family), and Lavandula angustifolia, Lavandula × intermedia, Melissa officinalis, Salvia officinalis, Salvia sclarea, and Salvia rosmarinus (from the Lamiaceae family) after steam distillation. The residual biomasses were extracted using ethanol (conventional solvent) and different natural deep eutectic solvents (NADES) composed of choline chloride in combination with citric and lactic acids at different molar ratios. The NADES containing choline chloride and lactic acid at the molar ratio 1:1 (CLA11) exhibited the highest recovery of representative phenols of the plants, namely chicoric and rosmarinic acids. The CLA11 solvent demonstrated a stronger extractive capacity compared to ethanol in all the biomasses belonging to the Asteraceae and Lamiaceae families. Specifically, CLA11 extracts showed a higher number of compounds in UHPLC-HRMS and greater concentrations of chicoric and rosmarinic acids determined by HPLC-DAD than ethanol extracts. In conclusion, NADES were demonstrated to be a viable alternative system for the recovery of bioactive compounds that could be used to formulate new products for the food, pharmaceutical, and cosmetic industries. Moreover, the use of NADES can enhance the sustainability of the whole production chain of essential oils being environmentally friendly.